CIRCULATING INTER-OPERATIONAL RESERVES: LONG-TIME ERRORS - G. A. Kalinkin (Наука и техника)
The paper shows that for dozens of years some researchers have presented a formula for calculating changes in circulating inter-operational reserve in the working phase of the flow production line in a wrong way as a formula for calculating a maximum change in the circulating inter-operational reserve of the working phase and the paper proposes an algorithm for calculation of circulating reserve in a boundary point of working phases of straight flow line. Having calculated a maximum change of the circulating reserve in the working phases it is possible to obtain an algebraic sum of reserve changes . After that the total algebraic sum of circulating reserve changes in boundary points from the initial phase to the final one. According to a minimum value of the algebraic sum of  the reserve changes in the phases it is possible to find a boundary point of phases where the reserve is equal to zero. A reserve in any boundary point  of  phases  is  calculated  through  finding  an  absolute value of the algebraic sum of reserve changes from boundary point of phases, where the reserve is equal to zero, to the sought one.